Evolutionary thanatology. (16th July 2018) - Anderson, James R.; Biro, Dora; Pettitt, Paul
Abstract : Societies, including those of humans, have evolved multiple ways of dealing with death across changing circumstances and pressures. Despite many studies focusing on specialized topics, for example necrophoresis in eusocial insects, mortuary activities in early human societies, or grief and mourning in bereavement, there has been little attempt to consider these disparate research endeavours from a broader evolutionary perspective. Evolutionary thanatology does this by adopting an explicit evolutionary stance for studies of death and dying within the sociological, psychological and biological disciplines. The collection of papers in this themed issue demonstrates the value of this approach by describing what is known about how various nonhuman species detect and respond to death in conspecifics, how problems of disposing of the dead have evolved in human societies across evolutionary time and also within much shorter time frames, how human adults' understanding of death develops, and how it is ultimately reflected in death-related language. The psychological significance and impact of death is clearly seen in some species' grief-like reactions to the loss of attachment figures, and perhaps uniquely in humans, the existence of certain psychological processes that may lead to suicide. Several research questions are proposed as starting points for building a more comprehensive picture of the ontogeny and phylogeny of how organisms deal with death. This article is part of the theme issue 'Evolutionary thanatology: impacts of the dead on the living in humans and other animals'.